Freddie Flintoff : My World - Flintoff, Andrew (London Hodder & Stoughton, 2006)
Andrew "Freddie" Flintoff, England's cricketing superstar, hero of the Ashes victory and British Sports Personality of the Year 2005, celebrates his rise to stardom with a large format, beautifully illustrated pictorial autobiography.
Include Color Illustrations.
Keywords: England -- Cricket -- Cricket players